Functional movement screen score to predict injury risk of sports students: a review of foot shape and body mass index - Khoiril Anam; Anies Setiowati; Nanang Indardi; Fajar Awang Irawan; Ratko Pavlović; Nugroho Susanto; Eva Ayu Aditia; Muhammad Muhibbi; Hendra Setyawan (IP Iermakov S.S., 2024)
Background and Study Aim. Excessive physical activity poses a risk of injury, particularly when coupled with high exercise intensity. Factors such as Body Mass Index (BMI) and foot morphology may contribute to this risk. This study seeks to evaluate the relationship between BMI, foot shape, and the likelihood of injury among sports students. Material and Methods.  A total of 119 sports students, comprising 33 females and 86 males, participated in this study. Purposive sampling was employed to select participants. BMI was determined using height and weight measurements, while foot shape was assessed through footprint measurements. The Functional Movement Screening (FMS) instrument, encompassing 7 movements: Deep Squats, Hurdle Steps, Inline Lunges, Shoulder Mobility, Active Straight Leg Raises, Trunk Stability Push-ups, and Rotary Stability, was utilized to assess injury risk. Data analysis was conducted using Microsoft Excel and IBM SPSS v.25.0, employing descriptive statistics. Results. Based on data analysis, the FMS value in females shows a mean of 18.7 and a standard deviation of 1.21. At the same time, the FMS value in males shows 18.5 and a standard deviation of 1.41. BMI values in females showed a mean of 21.6 and a standard deviation of 3.03. At the same time, BMI values in males showed a mean of 22.9 and a standard deviation of 4.62. The results  were that all FMS scores were ≥14. While  of BMI measurements, some samples obtained ˂18 kg/m² and ˃30kg/m². BMI measurements according to gender were mainly in the normal weight category. However, those who fall into the obesity category are primarily males.  With the results of measuring the foot's shape, the percentage of flat feet is only 0.84% in females and 7.59 in males, while the rest of the sample has a normal foot shape. Conclusions. Individuals with a BMI in the overweight to obese category are more susceptible to high-category injuries, likely due to limited motion range. However, the study did not find evidence linking flat foot shape to high-category injury risk. This inability to establish a correlation may be attributed to the predominantly normal foot shape observed in the sample, resulting in a prediction of low-category injury risk.